On a Report of Red-Bellied Pacu Piaractus brachypomus (Cuvier, 1818), (Characiformes: Characidae) from Muvattupuzha River, Kerala, India - Zeena, K. V.; Jameela Beevi, K. S. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.